Do International Tourist Arrivals Change Residents' Attitudes Towards Immigration? A Longitudinal Study of 28 European Countries - Artjoms Ivlevs; Ian Smith (Institute of Labor Economics (IZA), 2023)
Can international tourist arrivals change residents' attitudes towards immigrants and immigration? We discuss possible underlying mechanisms and provide the first evidence on this question using data from the European Social Survey (2002-2019; n=333,505). We find that, as tourist arrivals grow, residents become more positive towards immigration in Eastern Europe. In Western Europe, the relationship tends to turn from positive to negative at relatively high levels of tourism. The instrumental variable analysis suggests that incoming tourism has a positive causal effect on attitudes towards immigration in both Western and Eastern Europe. Overall, our study reveals an overlooked dimension of the tourism-migration nexus and highlights the role that international tourism may play in shaping attitudes towards immigration and, through these attitudes, immigration policy and flows, immigrant integration and more open and inclusive societies in tourism-receiving countries.
Keywords: J61; L83; 330; tourism; attitudes towards immigration; inclusion; Europe; instrumental variable analysis